1986
DOI: 10.1111/j.1600-0676.1986.tb00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements in normal and cirrhotic human liver tissue I. Iron, copper, zinc, selenium, manganese, titanium and lead measured by X‐ray fluorescence spectrometry

Abstract: ABSTRACT— Trace elements (Fe, Cu, Zn, Se, Mn, Ti, Pb) were measured by X‐ray fluorescence spectrometry in normal liver tissue obtained at autopsy from 74 subjects (44 ♀, 30 ♂), median age 62 years (range 20–87), and in tissue from 27 cirrhotic livers (14 alcoholic, 13 non‐alcoholic cirrhosis). The element content (median and 5–95 percentile interval) in normal livers in mmol/kg dry tissue was: Fe, 16.51 (7.82–39.03); Cu, 0.378 (0.189–0.629); Zn, 4.01 (2.59–9.33); Se, 0.018 (<0.004–0.035); Mn, <0.055 (<0.055–0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 24 publications
(8 reference statements)
3
16
0
1
Order By: Relevance
“…In normal liver tissue low variations for Fe, Cu and Zn were detectable, indicating a close homeostatic balance between these elements. These results are consistent with previously published data in normal liver tissue [29][30][31][32][33][34].…”
Section: Sensitivity Of Spectrometer For Liver Tissue Analysissupporting
confidence: 83%
See 1 more Smart Citation
“…In normal liver tissue low variations for Fe, Cu and Zn were detectable, indicating a close homeostatic balance between these elements. These results are consistent with previously published data in normal liver tissue [29][30][31][32][33][34].…”
Section: Sensitivity Of Spectrometer For Liver Tissue Analysissupporting
confidence: 83%
“…Mean values of the investigated elemental concentrations are given in Tab 2. The determined elemental concentrations for Fe, Cu and Zn in normal liver tissue by using a germanium-standard for their calculation were in line with previously published data mostly determined by using atomic absorption or X-ray fluorescence techniques [29,30]. In normal liver tissue low variations for Fe, Cu and Zn were detectable, indicating a close homeostatic balance between these elements.…”
Section: Sensitivity Of Spectrometer For Liver Tissue Analysissupporting
confidence: 71%
“…Disorders in zinc metabolism have been described in patients with chronic liver disease, and several studies found a decrease in plasma, serum or liver zinc concentrations (Loguercio et al, 2001;Halifeoglu et al, Schneider et al, 2009;Matsuoka et al, 2009, Milman et al, 1986Göksu & Özsoylu, 1986;Sharda & Bhandari, 1986;Bode et al, 1988;Kollmeier et al, 1992). The decrease of zinc in liver disease seems to be associated with decreased intake, poor absorption associated with portal hypertension, and greater urinary excretion (Loguercio et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Decreases in plasma (Halifeoglu et al, 2004;Schneider et al, 2009;Pereira et al, 2011) or serum (Hamed et al, 2008, Matsuoka et al, 2009) zinc concentrations have been described in patients with chronic liver diseases. Authors that measured zinc in the liver parenchyma of adults and children with liver cirrhosis found low zinc levels (Milman et al, 1986;Göksu & Özsoylu, 1986;Sharda & Bhandari, 1986;Kollmeier et al, 1992;Adams et al, 1994). In patients with alcoholic cirrhosis, studies found abnormal zinc concentrations not only in the liver parenchyma (Rodriguez-Moreno et al, 1997), but also in subcellular fractions of the liver (Bode et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that CHC patients show lower zinc concentrations in blood as their pathologic condition worsens from chronic hepatitis, to compensated cirrhosis, to decompensated cirrhosis, to hepatocellular carcinoma. Lower serum zinc concentrations in chronic liver diseases and zinc depletion have been suggested to be a cause of liver fibrosis (Milman et al, 1986;Bode et al, 1988). Zinc level in the serum is used clinically to indicate the viability of the liver, and recently it was used to enhance the response interferon therapy for CHC patients (Ishikawa, …”
Section: Discussionmentioning
confidence: 99%